Textbook Evaluation in Elementary Schools: An Approach Based on Early Childhood Development - Fadila, Meisyani Gustri; Rozimela, Yenni; Zainil, Yetti (Journal of English Education and Teaching, 2025)
In early English education, textbooks strongly influence children’s language acquisition and development. Yet, many prioritize cognitive skills while neglecting emotional and physical growth, limiting their suitability for young learners. This study evaluates the English textbook My Next Words, developed under Indonesia’s Merdeka Curriculum, through an early childhood development lens encompassing cognitive, emotional, and physical dimensions. Using a descriptive design, data were collected from textbook analysis and semi-structured interviews with five English teachers in Lengayang District, Pesisir Selatan Regency, West Sumatra. The data were then analyzed by measuring the percentage of each dimension of children’s development to present the majority from three dimensions. The results of this study revealed that while the textbook effectively supports cognitive development (74.1%), it provides minimal attention to emotional (18.5%) and physical (7.4%) growth. Teachers further reported that activities were repetitive and cognitively oriented, restricting creativity and hands-on engagement. These findings highlight a significant gap in English for Young Learners (EYL) resources, where textbooks often lack balance across developmental domains. The study contributes to EYL and textbook development by underscoring the need for more holistic materials that foster not only language skills but also children’s emotional and physical growth.